(untitled) (Zoological Records and Reviews, 2022)
Telangana, the youngest state of India carved from Andhra Pradesh in 2014, encompasses a diverse landscape of Deccan Plateau scrub, Eastern Ghats hill forests, riverine corridors along the Godavari and Krishna river systems, and semi-arid grasslands. Despite this habitat diversity, the spider fauna of Telangana remains poorly documented, with published records largely restricted to incidental observations in broader regional surveys. This study presents new distributional records for 84 spider species belonging to 28 families from 46 survey localities across Telangana, collected during systematic field surveys conducted between 2019 and 2021. Among the documented species, 34 represent new state records for Telangana, 12 are new records for peninsular India, and 3 are putative new species pending formal description. The families Salticidae (18 species), Araneidae (14 species), and Thomisidae (11 species) are the most species-rich in the regional fauna. Habitat associations are documented for all species, with deciduous hill forest habitats supporting the greatest species richness (62 species) and the highest proportion of new records (72%). Morphological descriptions and photographic documentation are provided for all new state and peninsular records. Updated distribution maps for 12 priority species are presented. The findings substantially expand knowledge of spider diversity in the Deccan Plateau biogeographic province and highlight Telangana’s forested uplands as a priority area for further arachnological exploration.